협대역 다중전송시스템에서의 등화 성능 - 유신우(Sinwoo Yo); 지영근(Younggun Ji); 조형원(Hyung-Weon Cho); 한철희(Chulhee Han); 서명환(Myunghwan Seo); 오혁준(Hyukjun Oh) (한국정보통신학회논문지, 2020)
In this paper, a multiple transmission communication system employing ranging based transmission timing adjustment capability is proposed. In addition, a decision feedback equalizer with the use of combinations of soft decision and hard decision adequate to the proposed multiple transmission communication system is also proposed. The proposed ranging based transmission timing adjustment capability makes the received signals from the multiple transmission points centered on the different symbol timing boundaries. The decision making method for the inputs to the proposed decision feedback equalizer is adaptively selected between soft decision and hard decision as per channel conditions like SNR. The performance of the proposed method had been analyzed through the simulation under the fading channel environments and compared with the previous methods. The simulation results showed performance improvement of the proposed method over the existing ones without noticeable increments in complexities. 본 논문은 협대역 다중전송시스템의 구조 및 다중전송에 적합한 등화기의 성능 분석에 관한 것으로서. 등화 성능의 극대화를 위하여 다중전송에 있어 레인징 기법에 기반한 전송 시점 제어 방법을 제안하고, 제안된 다중 전송기법에 적합한 연판정 및 강판정 조합 궤환 적응 판정 등화기를 제안하였다. 본 논문에서 제안하는 연판정 및 강판정 조합 궤환 적응 등화기는 SNR의 범위에 따라 궤환 적응 등화기의 입력으로 사용되는 판정 방법을 가변하는 것이다. 제안된 기법의 우수성을 입증하기 위하여 페이딩 채널 환경에서 모의실험을 통하여 제안된 방법의 성능을 검증하였다. 성능 검증결과, 기존 방법과 비교하여 본 논문에서 제안하는 방법이 큰 복잡도 증가 없이 기존 방법의 성능을 뛰어넘는 우수한 성능을 보임을 확인하였다.